Lead inhibits the odontogenic differentiation potential of dental pulp stem cells by affecting WNT1/β-catenin signaling and related miRNAs expression. (September 2022) - Khalid, Madiha; Hodjat, Mahshid; Baeeri, Maryam; Rahimifard, Mahban; Bayrami, Zahra; Abdollahi, Mohammad
Abstract: Lead (Pb) is ubiquitous in environment that accumulates in teeth and calcified tissues from where it releases gradually with aging and adversely affects dental health. This study aimed to determine the effect of Pb exposure on odontogenic differentiation potential of isolated human dental pulp stem cells and investigate the possible underlying epigenetic factors. In the absence of Pb exposure, stem cells displayed significant odontogenic markers including elevated Alkaline Phosphatase (ALP) activity, Alizarin red staining intensity, and increased expression of odontogenic DMP1 and DSPP genes. Exposure to 60 μM Pb resulted in reduced ALP activity and calcium deposition. Also, diminished expression of RUNX2, DMP1, and DSPP, as well as Wnt signaling mediators including WNT1, and β-catenin were detected. The expression of Wnt signaling related microRNAs, miRNA-139-5p and miRNA-142-3p, on the other hand, were shown to have a significant increase. We concluded that Pb could adversely affect the odontogenic differentiation potential of dental pulp stem cell. The underlying mechanism might related to Pb-induced epigenetic dysregulation of WNT1/β-catenin pathway-related miRNAs leading to down-regulation of Wnt/β-catenin related odontogenic genes and eventually impaired odontogenic differentiation process. Highlights: Lead could adversely affect the odontogenic differentiation potential of dental pulp stem cell. Lead reduces the expression of WNT1/β-catenin pathways related genes. Lead induce dysregulation of miRNA-139-5p and miRNA-142-3p.